Tribal constitutionalism states, tribes, and the governance of membership - Gover, Kirsty (Oxford : Oxford University Press, 2011)
This is a critical analysis of current political and sociolegal theories of tribalism and indigeneity which draws upon legal doctrine, policy, demographic data, and tribal practice to provide a comparative evaluation of tribal membership governance in the western settler states.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 11, 2011).
Keywords: Tribal government; Tribes -- Law and legislation; Indigenous peoples -- Legal status, laws, etc